Ethical dilemmas of kazakhstani journalists (Herald of Journalism, 2022)
A journalist is supposed to provide society with true, objective, balanced, up-to-date information and act fairly and impartially, be truthful and transparent. Otherwise, journalists may cause harm by failing to act ethically. The purpose of this research is to examine journalism ethics in Kazakhstan, explain probable reasons for ethical misbehavior and suggest possible solutions to the existing problems in journalistic ethics. It is an important study because journalism misbehavior affects everyone and little attention is given in research about journalism ethics in Kazakhstan. To address research inquiry, this research study uses qualitative structured interviews with 11 working journalists and editors in the country. The interviews were conducted in Russian language during the fall 2021. Convenience and snowball sampling were used in the study. Specifically, seven journalists working in independent media outlets, three journalists from state-owned media outlets and one journalist working in international media outlet, participated in the study. The sample consisted of five women and six men, ranging in age from 29 to 49 years old and having experience in journalism from seven to 25 years. The interviewees did not receive a monetary compensation for participation. The findings suggest that socio-economic, political and personal factors explain ethical misbehavior in journalism. As for probable solutions to the current problems in journalistic ethics, the majority of the respondents believe that the situation may be improved through teaching ethics in universities, holding training and professional workshops for everyone involved in journalism. Some journalists suggest that nothing needs to be done with ethics and instead it is necessary to solve some complex issues in society. The value of the conducted research lies in the study of the reasons for ethical misbehavior.Keywords: journalistic ethics, Kazakhstan, journalism, ethical principles, deontology.